2017
DOI: 10.1136/thoraxjnl-2016-208638
|View full text |Cite
|
Sign up to set email alerts
|

The evidence of benefits of exercise training in interstitial lung disease: a randomised controlled trial

Abstract: Background Uncertainty exists regarding the clinical relevance of exercise training across the range of interstitial lung diseases (ILDs). Objective To establish the impact of exercise training in patients with ILDs of differing aetiology and severity. Methods 142 participants with ILD (61 idiopathic pulmonary fibrosis (IPF), 22 asbestosis, 23 connective tissue disease-related ILD (CTD-ILD) and 36 with other aetiologies) were randomised to either 8 weeks of supervised exercise training or usual care. Six-minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
190
3
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(218 citation statements)
references
References 41 publications
11
190
3
14
Order By: Relevance
“…Physical rehabilitation has documented positive effects on general well-being and dyspnoea [51][52][53]. A precise assessment of the symptoms should be offered to all IPF patients and should be performed by an experienced physiotherapist with a 6-min walk test (6MWT) and validated tools; the same tools should be used to document the effect of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical rehabilitation has documented positive effects on general well-being and dyspnoea [51][52][53]. A precise assessment of the symptoms should be offered to all IPF patients and should be performed by an experienced physiotherapist with a 6-min walk test (6MWT) and validated tools; the same tools should be used to document the effect of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Physical rehabilitation can improve exercise tolerance, dyspnoea and QoL in patients with ILDs [24], and its effect is proven in patients with IPF [51][52][53]. Despite differences in the programmes, outcomes and scales used in the available studies and the open questions about the long-term effect of the intervention and on how to maximise its effect [54], physical rehabilitation is probably the safest and most effective treatment of dyspnoea, and is widely recommended for all patients with IPF [1].…”
Section: Dyspnoea and Exercise Capacitymentioning
confidence: 99%
“…As in other respiratory diseases, Dowman et al 12 found that baseline clinical variables were poorly predictive of the response to exercise training, and this work provides no basis for using pulmonary function markers of severity to exclude individuals with ILD from exercise training. In fact, those most limited at baseline tended to have the greatest short-term benefit from PR, a pattern that is also recognised in COPD13 and has been noted previously in ILD 14.…”
mentioning
confidence: 93%
“…There remain questions about the value of exercise training-based interventions in ILD in relation to both disease aetiology and severity. In Thorax , Dowman et al 12 report a randomised, controlled, assessor-blinded trial assessing the effectiveness of PR in 142 stable patients with exertional dyspnoea and a variety of ILD aetiologies. These were considered in three specific categories—asbestosis (n=22), idiopathic pulmonary fibrosis (IPF) (n=61) and connective tissue disease-related (CTD-ILD) (n=23).…”
mentioning
confidence: 99%
“…12,13 The evidence -based medicine has shown positive results in terms of quality of life, dyspnea, and exercise capacity of patients who have undergone a RRP. [14][15][16][17] The objective of this study is to demonstrate the effects of a respiratory rehabilitation program designed in primary care based on education, training of peripheral and respiratory musculature, respiratory physiotherapy and functional activities in a group of patients with ILD. Our research question is: Are there significant changes in the 6MWT, FVC, DLCO, initial oxygen saturation, final oxygen saturation, oxygen desaturation, dyspnea, MIP and quality of life of the patients with ILD after completing a respiratory rehabilitation program in primary care?.…”
Section: Introductionmentioning
confidence: 99%